1979
DOI: 10.1111/j.1471-4159.1979.tb11049.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: Deacetylation to 5‐methoxytryptamine by Liver but Not Brain Aryl Acylamidase

Abstract: Rat liver and brain slices were incubated it! r i m with ['H]melatonin. Liver slices synthesized small amounts of [3H]5-methoxyindoleacetic acid ([3H]5-MIAA) along with other melatonin metabolites including 6-hydroxymelatonin. Pretreatment of animals prior to killing with the irreversible monoaminc oxidase inhibitor pargyline allowed ['HIS-methox) tryptamine ([3H]S-MT) to be recovered from the incubation. No ['H]5-MIAA or ['HIS-MT could be detected in incubations with h>pothalamic slices or following intravent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…It has remained uncertain to what extent non-specific AAAs of vertebrate origin are capable of deacetylating melatonin at all. 5-MT formation from melatonin was reported for mammalian liver, whereas, in the same studies, no such conversion was observed in the brain [9,112].…”
Section: Melatonin Deacetylationmentioning
confidence: 72%
“…It has remained uncertain to what extent non-specific AAAs of vertebrate origin are capable of deacetylating melatonin at all. 5-MT formation from melatonin was reported for mammalian liver, whereas, in the same studies, no such conversion was observed in the brain [9,112].…”
Section: Melatonin Deacetylationmentioning
confidence: 72%
“…However, the melatonin-induced increase in the tissue level of serotonin can be seen in all of the brain structures studied of pargyline-treated rats with a partial lesion of the serotonergic system. Under these experimental conditions, the physiologic synthesis and storage of serotonin is diminished by the neurotoxin 5,7-DHT specific to the serotonergic system, and the amount of serotonin formed by an alternative pathway (via 5-MT O-demethylation by CYP2D) is raised due to a supply of an exogenous substrate (i.e., 5-MT formed from exogenous melatonin in the liver) (Rogawski et al, 1979;Beck and Jonsson, 1981), which crosses the blood-brain barrier (Acuña-Castroviejo et al, 2014). Moreover, both peripheral and brain 5-MT and serotonin formed from it are protected by intraperitoneal pargyline against MAO oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Being an amphiphilic substance, peripheral melatonin easily crosses the blood-brain barrier (Green et al, 1975). Circulating melatonin is metabolized mainly in the liver by cytochrome P450 isoforms of the CYP1A subfamily (CYP1A1/A2/B1) to form 6-hydroxymelatonin and then 6-sulfatoxymelatonin (Ma et al, 2005;Hardeland, 2010), but it can also be deacetylated to 5-methoxytryptamine (5-MT) (Rogawski et al, 1979;Beck and Jonsson, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin is also metabolized in the brain by indole-2,3-dioxygenase to give rise to N-acetyl-N'-formyl-5-methoxykynurenamine (Hirata et al 1974). Other minor metabolic 0004-9417/86/040427$02.00 pathways include demethylation to N-acetyl-5-hydroxytryptamine (Leone and Silman 1984) and deacetylation to 5-methoxytryptamine (Rogawski et al 1979).…”
Section: Introductionmentioning
confidence: 99%